HUBUNGAN PEMBERIAN IMUNISASI DASAR DENGAN TUMBUH KEMBANG PADA BAYI (0 – 1 TAHUN) DI PUSKESMAS KEMBES KECAMATAN TOMBULU KABUPATEN MINAHASA - Kaunang, Melisa C; Rompas, Sefti; Bataha, Yolanda (JURNAL KEPERAWATAN, 2016)
Abstract :Primary Immunization is very important to give towards the babies around 0-12 months in order for them to gain defense from preventing diseases with immunization which are Tuberculosis, Diphtheria, Pertussis, Tetanus, Polio, Hepatitis B and Measless. Provision of primary immunization is extremely affect against the baby grow development process. Grow and development are the things that very matters towards organism as an survival defend attempt and preserve the descent. Purpose, analyze the relationship between provision of primary immunization and growth of the baby and analyze the relationship between provision of primary immunization and development of the baby. Research Design, is an analytic observation, with cross sectional approach. Sample, taken by Total Sampling technic total 45 respondents. Results, the research on these two analyses is using chi-square test attained p value = 0,000 which is smaller than a = 0.05. The conclusion in this research that is there are relation between provision of primary immunization toward the baby’s growth and there is relation also between the provision of primary immunization with the baby’s development. Suggestion, can be useful as an information against the parents that has baby in order for them to know the importance of the provision of primary immunization toward baby that very impact the growth and development of the bab. Keywords : Primary Immunization, Growth, Development Abstrak :Imunisasi dasar sangat penting diberikan pada bayi berusia 0 – 12 bulan untuk memberikan kekebalan dari penyakit yang dapat dicegah dengan imunisasi (PD3I) antara lain Tuberkolosis, Difteri, Pertusis, Tetanus, Polio, Hepatitis B dan Campak. Pemberian imunisasi dasar sangat berpengaruh terhadap proses tumbuh kembang bayi. Pertumbuhan dan perkembangan merupakan hal yang sangat penting bagi makhluk hidup yaitu sebagai upaya untuk mempertahankan kelangsungan hidup dan melestarikan keturunan. Tujuan menganalisis hubungan pemberian imunisasi dasar dengan pertumbuhan bayi dan menganalisis hubungan pemberian imunisasi dasar dengan perkembangan bayi. Desain penelitian adalah observasional analitik, dengan pendekatan cross sectional. Sampel diambil dengan teknik Total Sampling yang berjumlah 45 responden. Hasil penelitian pada kedua analisis tersebut menggunakan uji chi-square diperoleh nilai p value = 0,000 yang lebih kecil dari á = 0,05. Kesimpulan pada penelitian ini yaitu terdapat hubungan pemberian imunisasi dasar dengan pertumbuhan bayi dan terdapat hubungan pemberian imunisasi dasar dengan perkembangan bayi. Saran dapat digunakan sebagai informasi kepadaorang tua yang memiliki bayi tentang pentingnya pemberian imunisasi dasar pada bayi berkaitan dengan pertumbuhan dan perkembangan bayi. Kata Kunci : Imunisasi Dasar, Tumbuh, Kembang.